Insulin Resistance as a Shared Pathogenic Mechanism Between Depression and Type 2 Diabetes - Lyra e Silva, Natalia de M.; Lam, Minh P.; Soares, Claudio N.; Munoz, Douglas P.; Milev, Roumen; De Felice, Fernanda G. (Frontiers in Psychiatry, 2019)
Neuropsychiatric disorders, type 2 diabetes (T2D) and obesity are major public health concerns that have been increasingly proposed to be intimately connected. T2D and obesity are associated with increased risk of neuropsychiatric and mood disorders, including diminished cognitive performance, and increased rates of depression, anxiety and dementia. More recently, molecular connections between depressive disorder, T2D and obesity have been established, since insulin resistance, a hallmark of type 2 diabetes, also develops in the brains of patients with depression. In this article, the possible molecular mechanisms underlying defective brain insulin signaling in depression are discussed, with emphasis on evidence that depression and some metabolic disorders share common inflammatory signaling pathways and hyperactivity of the hypothalamic-pituitary-adrenal (HPA) stress axis. We further discuss that novel insight into the link between insulin resistance and depression may advance the development of effective treatments for depression.